Implementation of Merdeka Curriculum: P5 Theme Build the Soul and Body Using Project-Based Learning - Setyawati, Nanik; Mulyanah, Mulyanah; Pamuningtyas, Astrilina; Arda Nugroho, Suryo Prakoso; Firdaus, Firdaus (Seutia Hukamaa Cendekia, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum in the context of the Pancasila Student Profile Strengthening Project (P5) with the theme